REAL-WORLD APPLICATIONS OF DIGITAL TWIN TECHNOLOGY IN PERFORMANCE MANAGEMENT: LESSONS FROM GLOBAL HEALTHCARE CASE STUDIES - Chouguiat Belmallem Saliha,; Koudoua Ferhati, (International Journal of Innovative Technologies in Social Science, 2025)
Digital twin technology is revolutionizing healthcare by providing a real-time digital replica of hospital systems, enabling better decision-making and performance optimization. This study examines the implementation of digital twin models in healthcare through an analysis of four real-world case studies: The Moorfields Eye Hospital (UK), Singapore General Hospital, Duke Health (USA), and The Karolinska University Hospital (Sweden). By reviewing these cases, the study highlights their impact on operational efficiency, resource utilization, and patient care outcomes. Challenges faced during implementation and key lessons learned are discussed to guide future adoption of digital twin technology in healthcare.